Pour un retour de la personne grammaticale dans l’analyse narratologique - Arthur Brügger (Cahiers de Narratologie)
This article argues for a return of the designation “X-person narrative” in literature research and university teaching, drawing in particular on its still frequent use in secondary school teaching. In addition to its accessibility, the “grammatical person” is a decisive clue to the stylistic, generic or thematic functioning of the narrative instance constructed by the story. For narratology, such a return implies a change of focus, from the narrator to the protagonist(s) of the literary narrative. In the course of its argument, this article lists the benefits of such an approach, guided by the identification of the pronoun(s) involved in a textual sequence, from both a pedagogical and epistemological point of view. Finally, an examination of the narrative situation in Maryse Condé's Traversée de la Mangrove (1989) shows how indecision on the question of the narrator offers hermeneutical advantages, inviting us to reconsider the question of the narrative voice (“who speaks?”) as a pragmatic and interpretative issue rather than a theoretical debate to be resolved.